PENGARUH EARNING PER SHARE DAN RETURN ON ASSET TERHADAP HARGA SAHAM PADA PT. BANK NEGARA INDONESIA TBK PERIODE 2009-2018 - Agus Suhartono; Waluyo Jati; Denok Sunarsi (Pascasarjana Universitas Halu Oleo, 2019)
This study aims to determine the effect of Earning Per Share and Return on Assets on Share Prices at PT. Bank Negara Indonesia Tbk. The method used is explanatory research with a sample of 10 years of financial statements. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Earning Per Share have a significant effect on stock prices by 51.2%, hypothesis testing obtained significance of 0.015 < 0.05. Return on Assets does not have a significant effect on stock prices, the contribution of influence of 33.9%, the hypothesis test obtained significance of 0.047 < 0.05. Earning Per Share and Return on Assets simultaneously have a significant effect on stock prices by 73.2%, hypothesis testing obtained significance of 0.010 <0.05.